Goal adjustment influence on psychological well‐being following advanced breast cancer diagnosis. Issue 1 (18th June 2015) - Lam, Wendy W. T.; Yeo, Winnie; Suen, Joyce; Ho, Wing Ming; Tsang, Janice; Soong, Inda; Yau, Tze Kok; Wong, Ka Yan; Sze, Wing Kin; Ng, Alice W. Y.; Kwong, Ava; Suen, Dacita; et al.
Abstract: Objective: A diagnosis of advanced breast cancer (ABC) challenges a woman's ambitions. This longitudinal study explored (1) if goal adjustment disposition influenced psychological adjustment patterns among women with ABC and (2) if dispositional hope and optimism moderate effects of goal adjustment on psychological adjustment. Methods: One hundred ninety three out of 225 women with ABC were assessed while they were awaiting/receiving initial chemotherapy, then again at 6 weeks, 3 months, 6 months, and 12 months post‐baseline. Goal disengagement, goal reengagement, optimism, hope, and psychological adjustment (anxiety, depression, and positive affect) were assessed at baseline; psychological adjustment was reassessed at each follow‐up. Latent growth curve modeling was used to examine the change of psychological adjustment and test the study objectives. Results: High goal disengagement, low reengagement, and high optimism were associated with lower initial anxiety, while high goal disengagement and optimism predicted a slower rate of change in anxiety. High goal disengagement, reengagement, and optimism were associated with lower initial depression. High goal reengagement, optimism, and hope were associated with initial positive affect scores, while optimism predicted its rate of change. Optimism moderated the effect of goal disengagement on anxiety and depression, whereas hope moderated the effect of goal reengagement on positive affect. Conclusion: Goal disengagement and reengagement are two relatively independent processes influencing psychological well‐being. These findings will help clinicians to tailor specific interventions to help women coping with the diagnosis of ABC. Copyright © 2015 John Wiley & Sons, Ltd.